Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.